Teknologi Kesehatan Digital Dalam Penanganan Masalah Diabetes Melitus Literature Review - Safaruddin Safaruddin; Henny Permatasari (Universitas Malahayati Lampung, 2022)
ABSTRACT Diabetes mellitus (DM) is a chronic disease in the form of metabolic disorders with increased blood sugar levels. The World Health Organization (WHO) reports that diabetes is a serious long-term condition with a major impact on the lives and well-being of individuals, families, and communities around the world. Diabetes is one of the top 10 causes of death in the world and is estimated to have caused four million deaths globally in 2017. The global prevalence of diabetes mellitus in 2019 was estimated at 463 million, increasing to 578 million in 2030 and 700 million by 2045. One in two people living with DM does not know they have DM. To collect and analyze articles related to the use of digital technology in supporting the handling of DM. The research design uses a literature review, the journals used in this study are journals published in 2015-2020 both qualitatively and quantitatively using online databases such as EBSCO, Science Direct, Proquest, and Oxford Academic which discuss the topic with the keyword “Information System. Diabetes and Nursing Information System and Diabetes, Health Technology and Diabetes. A total of 12 journals related to keywords. Overall, the journals obtained focus on the use of digital technology used for diabetes care. The use of digital health technology in supporting the handling of DM problems plays an important role in the modern world of health because it can function to improve health through applications that contain health information features related to diabetes. Digital technology offers various advantages and great benefits of providing a low-cost and effective solution for the management of DM. Suggestions for conducting in-depth research, especially the application of Digital Technology in supporting quality and comprehensive DM services. Keywords: Health Technology, Diabetes Information System, Diabetes and Health Information System ABSTRAK Diabetes mellitus (DM) adalah penyakit kronis berupa gangguan metabolisme dengan peningkatan kadar gula darah. Organisasi Kesehatan Dunia (WHO) melaporkan bahwa diabetes adalah kondisi jangka panjang yang serius dengan dampak besar pada kehidupan dan kesejahteraan individu, keluarga, dan masyarakat di dunia. Diabetes adalah salah satu dari 10 penyebab kematian teratas di dunia dan diperkirakan telah menyebabkan empat juta kematian secara global pada tahun 2017. Prevalensi global diabetes mellitus pada tahun 2019 diperkirakan mencapai 463 juta, meningkat menjadi 578 juta pada tahun 2030 dan 700 juta pada tahun 2045. Satu dari dua orang yang hidup dengan DM tidak tahu mereka memiliki DM. Ini mencerminkan peningkatan faktor risiko yang terkait dengan obesitas. Teknologi digital telah mengubah perawatan kesehatan secara global, seperti yang disaksikan oleh pertumbuhan di beberapa bidang kesehatan. Tujuan: Untuk mengumpulkan dan menganalisis artikel yang berkaitan dengan penggunaan teknologi digital untuk mendukung penanganan DM. Metode: Desain penelitian menggunakan tinjauan literatur, jurnal yang digunakan dalam penelitian ini adalah jurnal yang diterbitkan 2015-2020 baik kualitatif maupun kuantitatif menggunakan database online seperti EBSCO, Science Direct, Proquest, dan Oxford Academic yang membahas topik dengan kata kunci